Critical Literacy development through the use of sketchbooks in a rural EFL classroom (2024)
This study explores the use of sketchbooks as a multimodal learning strategy to describe its role in promoting critical literacy (CL) among teenage English as a Foreign Language (EFL) learners in rural Antioquia (Colombia). Using action research methodology, the study was conducted in a public rural institution, integrating multimodal pedagogy and texts to foster critical engagement with their own socio-cultural realities. Data were collected through observations, student-created sketchbooks, and focus group discussions. Three key findings emerged: (1) The influence of students' involvement with sketchbooks on CL development; (2) the correlation between context-specific materials and learners' sociocultural awareness; and (3) the double-edged role of native language in foreign language acquisition. This research underscores the need for innovative approaches to language learning that encompass critical engagement with sociocultural realities, thus proposing the sketchbooks and challenging future researchers to explore additional implementation cycles of this research, balancing CL development with EFL proficiency in rural settings.